Comprehensive Literature Review : Analisis Persepsi Pasien dan Kualitas Layanan terhadap Inovasi Layanan Rumah Sakit melalui Telemedicine - Mariyam, Dewi; Kustiani, Lilik; Estikowati (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2025)
Telemedicine has become an important innovation in healthcare services, especially in increasing patient accessibility to medical services. This study aims to analyze patient perceptions and service quality towards the implementation of telemedicine in hospitals. The method used is a comprehensive literature review, by analyzing various academic literature that discusses patient perceptions, dimensions of service quality, and challenges in implementing telemedicine. This study focuses on five dimensions of service quality, namely assurance, assurance, physical evidence, empathy, and responsiveness, and how these aspects affect patient experience and satisfaction. The results of the analysis show that patient perceptions of telemedicine are highly dependent on technological fitness, ease of access, and trust in medical personnel who provide consultations. In addition, patients prioritize aspects of data security and diagnostic accuracy, which are key factors in accepting telemedicine as an alternative healthcare service. Although telemedicine provides benefits such as ease of access and time efficiency, this study also found several challenges in its implementation. The gap in digital infrastructure, limited technological literacy among patients, and the need for stronger regulations are the main obstacles that need to be overcome. Therefore, the development of telemedicine in hospitals must focus on improving service quality, educating patients, and policies that support service desires.